2013
DOI: 10.1186/1471-2482-13-26
|View full text |Cite
|
Sign up to set email alerts
|

Routine histopathology of gallbladder after elective cholecystectomy for gallstones: waste of resources or a justified act?

Abstract: BackgroundSelective approach for sending cholecystectomy specimens for histopathology results in missing discrete pathologies such as premalignant benign lesions such as porcelain gallbladder, carcinoma-in-situ, and early carcinomas. To avoid such blunders therefore, every cholecystectomy specimen should be routinely examined histologically. Unfortunately, the practice of discarding gallbladder specimen is standard in most tertiary care hospitals of Pakistan including the primary investigators’ own institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
61
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 10 publications
(10 reference statements)
13
61
2
2
Order By: Relevance
“…None of the pts in T1 stage carcinoma had perineural invasion. Similar results were obtained in studies by Siddiqui and Ghnnam et al [10,14].…”
Section: Discussionsupporting
confidence: 91%
“…None of the pts in T1 stage carcinoma had perineural invasion. Similar results were obtained in studies by Siddiqui and Ghnnam et al [10,14].…”
Section: Discussionsupporting
confidence: 91%
“…Only one study by Siddiqui et al matches the incidence as found by this study. 27 Some studies have however depicted an incidence of 0.3-1.5% which is lower than the rate of this study. 30,31 Conversely, other studies have depicted a higher prevalence rate such as 6.9 -12.3 %.…”
Section: Discussioncontrasting
confidence: 49%
“…25,26 Majority of the patients were found to have presented with pain in the abdomen which is consistent with the findings of Siddiqui et al and slightly different from the reports of Fletcher et al who reported that all patients presented with pain. 27,28 With respect to the histopathological findings, the most common finding that was seen was acute cholecystitis (51%) followed by chronic cholecystitis(46%) with 3% depicting adenocarcinoma. Specimens reportedly had inflammation presenting with mucosal denudation, ulceration with some reports of metaplasia to dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, the necessity of histological analyses for all gallbladder specimens has been questioned. 1,4 Simple cholecystectomy can be regarded as adequate treatment of all benign and early malignant T1 gallbladder lesions.…”
mentioning
confidence: 99%